Clinical development prospects of siRNA drugs for tumor therapy: analysis of clinical trial registration data from 2004 to 2024 - Wang, Cai-E.; Zhen, Delong; Yang, Lukui; Li, Guifang (Frontiers in Pharmacology, 2025)
BackgroundThis study systematically compares clinical trial patterns of siRNA drugs in oncology and non-oncology, aiming to inform optimized R&D strategies for oncology.MethodsTrial phases, sponsor countries, biomarkers, and targets were analyzed for global siRNA trials (2004–2024).ResultsNon-oncology trial dominated (90% of 424 trials), peaking in 2021 (64 trials), and yielded 6 approved drugs for metabolic/genetic diseases. Key non-oncology targets included PCSK9 and HBV. Oncology trials initiated later, primarily focusing on phase I/II studies (60% phase I), targeting solid tumors (40%) and CSF2-related therapies (40%). Clinical trial activity in China commenced in 2019, demonstrating acceleration in 2023, yet overall trial volume remains lower than global benchmarks. Cross-target analysis has pinpointed PTGS2 and TGFB1 as shared targets, indicating the possibility for combination therapy.ConclusionOvercoming technical challenges (e.g., targeted delivery) and exploiting multi-target synergies are critical to expanding siRNAs applications in oncology. Success in non-oncology settings demonstrates the translational potential of siRNA technology, however, oncology requires tailored strategies to address complex tumor biology and delivery barriers.